Individual differences explain regional differences in honor-related outcomes. (1st April 2018) - Saucier, Donald A.; Miller, Stuart S.; Martens, Amanda L.; O'Dea, Conor J.; Jones, Tucker L.
Abstract: Much research has been devoted to the investigation of both the culture of honor residing in the American South and the individual difference ideologies that stem from this culture. The purpose of our study was to investigate the ability of individual differences in masculine honor beliefs (Saucier et al., 2016) to explain the regional differences that Southern and Northern men showed on the original measures of honor-related outcomes employed by the seminal scholars in culture of honor research (e.g., Cohen & Nisbett, 1994; Nisbett, 1993). Consistent with hypotheses, our results replicate regional differences in honor-related responses, but also show that individual differences in masculine honor beliefs mediate these regional differences. Thus, our research extends the notion of cultures of honor beyond their regional boundaries, and highlights the value in conceptualizing honor as a psychological individual difference factor. Highlights: There are regional and individual differences in masculine honor ideology. Individual differences in masculine honor predict honor-related aggressive responses. Individual differences mediate regional differences in these aggressive responses.